PRAGMATICS : SPEECH ACTS AND THEIR ROLE IN COMMUNICATION (Modern education and development, 2025)
Speech act theory (J.L. Austin, J. Searle) categorizes utterances by function. It distinguishes locutionary, illocutionary, and perlocutionary acts, as well as direct and indirect speech acts. This paper highlights their significance in cross-cultural communication, artificial intelligence, and legal discourse.